Epidemiological profile of Schistosomiasis cases in Brazil between 2010 and 2017 (Research, Society and Development, 2022)
Schistosomiasis is a parasitic disease whose treatment has a series of limitations such as side effects and the emergence of parasitic resistance. It is known that several factors are determinant for schistosomal endemics in several regions of Brazil; however, the national epidemiological profile is still unclear. Thus, the present study aimed to carry out an epidemiological analysis of schistosomiasis cases in Brazil between the years 2010 to 2017. For this, data provided by the Sistema de Informação de Agravos de Notificação (SINAN), available on the Departamento de Informática do Sistema Único de Saúde (DATASUS). The findings indicate that, during the years 2010 to 2017, Brazil recorded 76,862 cases, which declined over the years. The disease was prevalent in males (61.11%), which may be related to the habits of these individuals, aged between 20 and 39 years (38.16%), mixed ethnicity/color (49.24%) and elementary school (40.54%). The state of Minas Gerais represented 70% of national cases. Positively, 63.82% of individuals with schistosomiasis managed to recover, with 511 deaths being recorded in the evaluated period. In conclusion, the data presented here demonstrate that the control of schistosomiasis has good results in Brazil, with a reduction in the number of cases and deaths over the years.